Negative pole piece, secondary battery and device

By optimizing the electrode structure in the negative electrode sheet of the secondary battery, combined with reasonable porosity, surface disorder, surface density and orientation, the problem of taking into account the charging speed and energy density of the secondary battery is solved, and the problem of taking into account the charging speed and energy density is achieved. 了高效快充和长续航的效果。

CN119447175APending Publication Date: 2025-02-14NIO TECH ANHUI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411586968.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing secondary batteries are difficult to balance the charging speed and energy density, resulting in insufficient range and long charging time of new energy vehicles.

Method used

By reasonably matching the porosity, surface disorder, surface density and orientation of the electrode sheet in the negative electrode sheet, the rapid transmission of lithium ions in the negative electrode sheet is ensured, and the secondary battery design including the negative electrode sheet is adopted, supporting 4C The above charging rate maintains high energy density and cycling performance.

Benefits of technology

It realizes fast charging performance of secondary batteries above 4C, and has high energy density and long cycle life, which improves the endurance and charging efficiency of new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124548900000101
    Figure BDA0005124548900000101
  • Figure BDA0005124548900000111
    Figure BDA0005124548900000111
  • Figure BDA0005124548900000112
    Figure BDA0005124548900000112
Patent Text Reader

Abstract

The invention provides a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises artificial graphite, and the negative electrode plate satisfies the following relational expression: 0 < = 3.6 * P + 2.6 * D 0.5-0.48 * ln W-0.55 * ln O < = 0.75, wherein P refers to the porosity of the negative pole piece; d refers to the surface disorder degree of the negative pole piece; w refers to the surface density of the negative pole piece, and the unit is mg / cm < 2 >; and O refers to the orientation degree of the negative pole piece. The secondary battery provided by the invention can support a charging rate of more than 4C and has relatively high energy density, and meanwhile, the pole piece structure is kept stable in a cycle process and has relatively long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a negative electrode plate, and in particular to a negative electrode plate, a secondary battery and a device including the secondary battery, belonging to the field of batteries. Background Art

[0002] In recent years, with the continuous improvement of environmental awareness and the transformation of energy structure, new energy vehicles have become the development direction of the automobile industry. In new energy vehicles, secondary batteries have been widely used as the main power source. However, problems such as long charging time and insufficient cruising range of secondary batteries have always plagued the development of new energy vehicles. Therefore, in order to improve the convenience and user experience of new energy vehicles, requiring secondary batteries to have good fast charging performance has become one of the necessary requirements for the development of new energy vehicles. Fast charging can greatly shorten the battery charging time and improve the charging efficiency, so that new energy vehicle users can charge faster and drive longer, thereby improving the competitiveness and market share of new energy vehicles. Therefore, secondary batteries with good fast charging performance have become an important direction and research hotspot for the development of new energy vehicles. At present, the main way to improve the fast charging performance of secondary batteries from the negative electrode level is to reduce the surface density of the negative electrode sheet and the compaction density of the electrode sheet, but the energy density of the secondary battery will decrease with the decrease of the surface density of the negative electrode sheet and the compaction density of the electrode sheet, thereby affecting the cruising range of new energy vehicles. Therefore, it is still a difficult problem to improve the fast charging rate of the battery from the negative electrode level of the secondary battery, while taking into account the higher energy density and cycle performance.

[0003] Therefore, there is an urgent need to develop novel secondary batteries with improved fast charging performance, energy density and cycle performance. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present application provides a negative electrode plate, a secondary battery and a device including the secondary battery. The present application ensures that lithium ions still have a relatively fast transmission speed in the negative electrode plate at a suitable surface density by reasonably matching the plate porosity, surface disorder, surface density and orientation. The secondary battery including the negative electrode plate can be charged at a rate of more than 4C, while having a high energy density and cycle performance.

[0005] The first aspect of the present application provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising artificial graphite, and the negative electrode plate satisfies the following relationship: 0≤3.6×P+2.6×D 0.5-0.48×ln W-0.55×ln O≤0.75, where P refers to the porosity of the negative electrode sheet; D refers to the surface disorder of the negative electrode sheet, where the surface disorder is the intensity ratio of the D peak and the G peak of the artificial graphite; W refers to the surface density of the negative electrode sheet, in mg / cm 2 ; O refers to the orientation degree of the negative electrode plate, wherein the orientation degree is the peak area ratio of the diffraction peak of the 004 crystal plane of the artificial graphite and the diffraction peak of the 110 crystal plane.

[0006] A second aspect of the present application provides a secondary battery, which includes the negative electrode plate and the positive electrode plate of the first aspect.

[0007] A third aspect of the present application provides a device comprising the secondary battery according to the second aspect.

[0008] The secondary battery of the present application can support a charging rate of more than 4C and has a higher energy density. At the same time, the electrode structure remains stable during the cycle and has a longer cycle life. DETAILED DESCRIPTION

[0009] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.

[0010] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0011] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0012] The term "surface disorder degree of the negative electrode sheet" refers to the intensity ratio of the D peak and the G peak of the artificial graphite in the negative electrode sheet measured by Raman spectroscopy.

[0013] The term "degree of orientation of the negative electrode sheet" refers to the ratio of the peak area C004 of the 004 plane and the peak area C110 of the 110 plane of the artificial graphite in the negative electrode sheet measured by X-ray diffraction.

[0014] 1. Negative electrode

[0015] The negative electrode sheet provided in the present application includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes artificial graphite, and the negative electrode sheet satisfies the following relationship: 0≤3.6×P+2.6×D 0.5 -0.48×ln W-0.55×ln O≤0.75, where P refers to the porosity of the negative electrode sheet; D refers to the surface disorder of the negative electrode sheet, where the surface disorder is the intensity ratio of the D peak and the G peak of the artificial graphite; W refers to the surface density of the negative electrode sheet, in mg / cm 2 ; O refers to the orientation of the negative electrode sheet, wherein the orientation is the peak area ratio of the diffraction peak of the 004 crystal plane of the artificial graphite to the diffraction peak of the 110 crystal plane. The present application makes the surface disorder of the electrode sheet and the orientation of the electrode sheet in a suitable range by rationally selecting the negative electrode active material, and controls the porosity of the electrode sheet at the same time, so that the porosity, surface density, surface disorder and orientation of the electrode sheet satisfy a certain relationship. Specifically, at a higher surface density, the appropriate surface disorder of the electrode sheet ensures that lithium ions are quickly embedded into the negative electrode active material through the surface of the negative electrode sheet, the appropriate porosity ensures that lithium ions migrate quickly in the electrolyte in the negative electrode sheet, and the appropriate orientation of the electrode sheet ensures the rapid transmission of lithium ions in the active material, maintaining a certain pore structure. Therefore, the present application improves the transmission speed of lithium ions in the pores of the negative electrode sheet and inside the negative electrode active material through the mutual coordination between the surface disorder, orientation, porosity and surface density of the negative electrode sheet, so that the negative electrode sheet has a higher fast charging performance. The secondary battery of the present application can support a charging rate of more than 4C and has a higher energy density. At the same time, the electrode structure remains stable during the cycle and has a longer cycle life.

[0016] In some embodiments, 3.6×P+2.6×D 0.5-0.48×ln W-0.55×ln O is 0, 0.01, 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.75 or any range therebetween. If the value is too small, the fast charging capability of the battery cell is insufficient; if the value is too large, the energy density of the battery cell is low. In some embodiments, 0≤3.6×P+2.6×D 0.5 -0.48×ln W-0.55×ln O≤0.6.

[0017] In some embodiments, 15≤P×E≤45, where E refers to the compression modulus of the negative electrode sheet, in MPa; if the P×E value is too small, the negative electrode sheet will have insufficient pores during the charge and discharge cycle, and the battery capacity will decay rapidly; if the P×E value is too large, the active material on the negative electrode sheet will easily fall off during the slitting, die cutting or winding process, resulting in a low battery manufacturing yield. In some embodiments, P×E is 15, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 45 or any range therebetween; in some embodiments, 20≤P×E≤40.

[0018] In some embodiments, 15%≤P≤45%; if the value is too small, the pores of the negative electrode plate are small, which is not conducive to the liquid phase diffusion of lithium ions in the negative electrode plate, and the fast charging ability of the battery is poor; if the value is too large, the volume energy density of the battery is low. In some embodiments, P is 15%, 20%, 25%, 30%, 35%, 40%, 45% or any range therebetween; in some embodiments, 20%≤P≤45%.

[0019] In some embodiments, 0.1≤D≤0.6; if the D value is too small, the fast charging capability of the battery is poor; if the D value is too large, the cycle performance of the battery is poor. In some embodiments, D is 0.1, 0.2, 0.3, 0.33, 0.36, 0.4, 0.42, 0.46, 0.48, 0.5, 0.55, 0.6 or any range therebetween; in some embodiments, 0.1≤D≤0.5.

[0020] In some embodiments, 12≤W≤30; if W is too small, the energy density of the battery is low, and if W is too large, the fast charging capability of the battery is poor. In some embodiments, W is 8, 12, 16, 20, 24, 28, 30 or any range therebetween; in some embodiments, 15≤W≤25.

[0021] In some embodiments, 3≤O≤20; if the O value is too small, the energy density of the battery is low, and if the O value is too large, the fast charging capability of the battery is poor. In some embodiments, O is 3, 6, 9, 12, 15, 18, 20 or any range therebetween; in some embodiments, 5≤O≤15.

[0022] In some embodiments, 20≤E≤300; if the E value is too small, the strain of the negative electrode plate during the battery charging and discharging process is large, and the battery cycle performance is poor; if the E value is too large, the processing performance of the negative electrode plate is poor, and it cannot be assembled into a qualified battery. In some embodiments, E is 20, 40, 50, 60, 70, 80, 100, 120, 140, 160, 180, 200, 250, 300 or any range therebetween; in some embodiments, 30≤E≤200. The appropriate plate compression modulus ensures that the deformation of the negative electrode plate during the cycle is small.

[0023] In some embodiments, the negative electrode active material further includes a silicon-based material.

[0024] In some embodiments, the silicon-based material includes at least one of silicon, silicon alloys, silicon-carbon compounds, silicon-oxygen compounds, and composites of elemental silicon and graphite.

[0025] In some embodiments, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a nickel-cobalt-based ternary material and a phosphate-based material.

[0026] In some embodiments, the nickel-cobalt ternary material includes LiNi m Co n At least one of A(1-mn)O2 materials, A is selected from at least one of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver and niobium, 0.5≤m≤1, 0≤n≤0.5, m+n≤1.

[0027] In some embodiments, m is 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or a range consisting of any two of these values. In some embodiments, n is 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or a range consisting of any two of these values.

[0028] In some embodiments, the nickel-cobalt-based ternary material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, or Ni95.

[0029] In some embodiments, the phosphate-based material includes LiMnk B (1-k) PO4, wherein 0≤k≤1, and the B element is selected from at least one of iron, cobalt, magnesium, calcium, zinc, chromium, or lead. In some embodiments, k is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or a range consisting of any two of these values. In some embodiments, the phosphate-based material includes lithium iron phosphate, LiMn 0.6 Fe 0.4 PO4 and LiMn 0.8 Fe 0.2 At least one of PO4.

[0030] In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

[0031] The surface of the positive electrode active material may have a coating, or may be mixed with another compound having a coating. The coating may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound used for the coating may be amorphous or crystalline. The coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive electrode active material. For example, the method may include any coating method well known to those of ordinary skill in the art, such as spraying, dipping, etc.

[0032] The positive electrode active material layer also includes a binder, which includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, styrene butadiene rubber or acrylic (ester) styrene butadiene rubber, etc.

[0033] The positive electrode active material layer also includes a conductive agent. The conductive agent includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. In some embodiments, the carbon-based material is selected from graphite, carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, graphene, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0034] The positive electrode plate also includes a positive current collector, which can be a metal foil or a composite current collector. For example, aluminum foil can be used. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.

[0035] In some embodiments, the negative electrode includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium, wherein the proportion of the carbon-based material in the active material is above 50%.

[0036] In some embodiments, the negative electrode active material layer further comprises a binder. In some embodiments, the binder comprises, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.

[0037] The negative electrode active material layer also includes a conductive agent. In some embodiments, the conductive agent can use any conductive material as long as it does not cause chemical changes. In some embodiments, the conductive agent includes, but is not limited to: at least one of a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. In some embodiments, the carbon-based material includes natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material includes metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer includes a polyphenylene derivative. In some embodiments, the conductive agent is preferably conductive carbon black.

[0038] The negative electrode active material layer further includes a thickener. The thickener includes, but is not limited to, at least one of sodium carboxymethylcellulose, lithium carboxymethylcellulose, polyacrylate, hydroxypropyl methylcellulose, and polyvinyl alcohol. In some embodiments, the thickener is preferably sodium carboxymethylcellulose or lithium carboxymethylcellulose.

[0039] In some embodiments, the negative electrode further includes a negative electrode current collector, and the negative electrode current collector includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.

[0040] In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator that can be used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed by a material that is stable to the electrolyte of the present application. In some embodiments, the separator can be selected from polyethylene film, polypropylene film, polyvinylidene fluoride film and their multilayer composite films.

[0041] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0042] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0043] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0044] The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).

[0045] When the secondary battery is a lithium-ion secondary battery, a lithium salt solution dissolved in an organic solvent is usually used as a non-aqueous electrolyte. The lithium salt may be an inorganic lithium salt (e.g., LiClO4, LiPF6, LiBF4, LiAsF6, LiSbF6), or an organic lithium salt (e.g., LiCF3SO3, LiCF3CO2, Li2C2F4(SO3)2, LiN(CF3SO2)2, LiC(CF3SO2)3, LiCnF2n+1SO3 (n≥2)). The organic solvents used in the non-aqueous electrolyte include cyclic carbonates (such as ethylene carbonate, propylene carbonate, butylene carbonate or vinylene carbonate), chain carbonates (such as dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate), (chain esters, such as methyl propionate), cyclic esters (such as γ-butyrolactone), dimethoxyethane, chain ethers (such as diethyl ether, diethylene glycol dimethyl ether or triethylene glycol dimethyl ether), cyclic ethers (such as tetrahydrofuran or 2-methyltetrahydrofuran), acetonitrile, propionitrile or a combination thereof.

[0046] Lithium-ion secondary batteries are composed of negative electrode plates, positive electrode plates, separators and electrolytes. The positive and negative electrodes are immersed in the electrolyte. Lithium ions move between the positive and negative electrodes with the electrolyte as the medium to realize the charging and discharging of the battery. In order to avoid short circuits between the positive and negative electrodes through the electrolyte, a separator is required to separate the positive and negative electrodes. The shape of lithium-ion secondary batteries can be, for example, a cylindrical (square cylindrical or cylindrical) with an aluminum shell or a steel shell as the outer shell, or a soft-pack battery with an aluminum-plastic film as the outer shell.

[0047] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0048] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft shell, and the material of the soft shell may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0049] The present application does not impose any specific restrictions on the type of secondary battery, and the secondary battery may be any type, such as a button-type, cylindrical, or soft-pack secondary battery.

[0050] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.

[0051] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0052] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0053] 2. Device

[0054] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module and battery pack.

[0055] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.

[0056] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0057] Examples and Comparative Examples

[0058] In order to make the purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with the examples. However, it should be understood that the examples of the present application are only for explaining the present application, not for limiting the present application, and the examples of the present application are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.

[0059] The artificial graphites in the following examples and comparative examples are all commercially available.

[0060] Example 1

[0061] Preparation of negative electrode sheet: artificial graphite, conductive carbon black (Super P), thickener carboxymethyl cellulose (CMC), binder (SBR) are mixed in a mass ratio of 96.2:0.8:1.2:1.8, dissolved in a solvent (deionized water), mixed evenly under the action of a vacuum mixer to prepare a negative electrode slurry, and the negative electrode slurry is evenly coated on both sides of a negative electrode current collector copper foil with a thickness of 6 μm, dried in an oven, rolled by a roller press, and cut to obtain a negative electrode sheet. The compacted density of the negative electrode sheet is 1.60 g / cm 3 , surface density is 19.0mg / cm 2 .

[0062] Preparation of positive electrode sheets: The positive electrode active material LiFePO4, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.2:0.6:2.2, and the solvent N-methylpyrrolidone (NMP) is added, and the system is stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the double-side surface of the positive electrode current collector aluminum foil with a thickness of 14μm; after drying at room temperature, it is transferred to an oven for drying, and then cold pressed and cut to obtain positive electrode sheets.

[0063] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 as a solvent, and fully dried lithium salt LiPF6 is dissolved in the solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0064] Preparation of isolation film: A 10 μm thick polyethylene film was selected.

[0065] Preparation of secondary batteries: stack the aforementioned positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain an electrode assembly, place the electrode assembly in an outer packaging shell, dry and remove moisture, inject the aforementioned prepared electrolyte, and obtain a secondary battery through vacuum packaging, standing, formation, shaping, capacity testing and other processes.

[0066] Examples 2 to 10 and Comparative Examples 1 to 2 are achieved on the basis of Example 1 by selecting appropriate negative electrode active materials to adjust the surface disorder, orientation and compression modulus, as well as adjusting the compaction density, surface density and porosity of the negative electrode sheet. Specific adjustment measures and detailed data are shown in Table 1.

[0067] Test method:

[0068] 1. Determination of the porosity of the negative electrode sheet

[0069] The porosity of the pole piece is measured by the gas displacement method (i.e., the compressed air method). Specifically, the thickness of 15 points on the pole piece is measured at fixed intervals to obtain the average thickness h1 of the pole piece, and then the thickness of the copper foil at 15 points is measured to calculate the average thickness h2 of the copper foil. 60 to 80 pole piece samples punched into small discs with a diameter of 19 mm are placed in a true density tester, and helium is used as the medium. The actual volume V0 of the sample is accurately determined by measuring the reduction in the capacity of the sample test cavity caused by the sample being placed in the sample test cavity. The apparent volume V of the material is then calculated based on the pole piece sample diameter, the average thickness of the pole piece, and the number of small discs of the pole piece. The porosity (P) is calculated according to the following formula: P = 100 × ((V-V0) / V × h1-h2) / (h1-h2)

[0070] 2. Determination of negative electrode orientation

[0071] The orientation of the negative electrode piece is tested by an X-ray diffractometer. In the X-ray diffraction analysis test, a copper target can be used as the anode target, and a Ni filter with a thickness of 0.02 mm is used to filter CuKβ. CuKα rays are used as the radiation source, and the ray wavelength (the weighted average of Kα1 and Kα2) is taken. The scanning 2θ angle range is 20° to 80°, and the scanning rate is 5° / min. In the present application, specifically, the test method for the orientation degree O value of the negative electrode piece is: the prepared negative electrode piece is directly placed in the X-ray diffractometer, and the peak area C004 of the 004 crystal plane diffraction peak of the graphite in the negative electrode active material in the negative electrode piece and the peak area C110 of the 110 crystal plane diffraction peak are obtained by X-ray diffraction analysis. The orientation degree O of the negative electrode piece is C004 / C110. The 2θ angle corresponding to the 004 crystal plane of graphite is 53.5° to 55.5° (eg, 54.5°); the 2θ angle corresponding to the 110 crystal plane of graphite is 76.5° to 78.5° (eg, 77.4°).

[0072] 3. Determination of disorder of negative electrode sheet

[0073] The disorder of the negative electrode is tested by a micro-confocal laser Raman spectrometer. The Raman spectra of at least 1600 points within the range of 500×500μm on the negative electrode are tested by a micro-confocal laser Raman spectrometer to obtain the Raman spectrum of each point, and the intensity ratio of the graphite D peak and the graphite G peak of each point is calculated according to the Raman spectrum of each point, wherein the D peak is in the range of 1300cm-1 to 1400cm-1, and the G peak is in the range of 1580cm-1 to 1620cm-1. According to the distribution of the intensity ratio of the graphite D peak and the graphite G peak at all points, the median of the intensity ratio of the graphite D peak and the graphite G peak is obtained, which is recorded as the disorder of the electrode D.

[0074] 4. Determination of negative electrode surface density

[0075] The negative electrode sheet surface density refers to the surface density of the negative electrode film on both sides of the negative electrode current collector (controlled by coating weight), and can be tested by methods known in the art.

[0076] 5. Determination of compression modulus of negative electrode

[0077] The compression modulus of the negative electrode is measured by a tensile testing machine. First, the electrode is cut into several discs with a diameter of D = 19 mm. The average thickness d of 40 discs is measured with a micrometer. Then, the 40 discs are stacked into a cylindrical sample. The height of the sample is h = 40 × d. The cylindrical sample stacked with the discs is placed in the center of the compression disc of the tensile testing machine so that the load center is consistent with the axial center line of the sample. The distance between the upper and lower discs of the compression device is adjusted to be equal to the height h of the sample. The force value of the tensile testing machine is reset to zero, and data is collected from 0N. The sample is continuously loaded at a loading rate of 2mm / min, and the data is continuously measured and recorded in the and-only data until the load reaches 90% of the full load of the force sensor or the sample is destroyed and the test is stopped; the compressive stress σ is calculated according to the following formula:

[0078]

[0079] Where:

[0080] σ represents the compressive stress of the specimen, in MPa;

[0081] P represents the load borne by the specimen, in N;

[0082] D represents the compressed cross-sectional diameter of the sample, that is, the disc diameter D, in mm.

[0083] The compressive strain ε is calculated as follows:

[0084]

[0085] Where:

[0086] ε represents the compressive strain of the specimen, dimensionless;

[0087] Δh represents the reduction in the initial spacing of the compression device corresponding to the load increment ΔP, in mm;

[0088] h represents the initial spacing of the compression device, in mm.

[0089] The compression modulus of the pole piece is calculated according to the following formula:

[0090]

[0091] Where:

[0092] E represents the compression modulus of the pole piece sample, in MPa;

[0093] σ1 represents the compressive stress corresponding to the strain value ε1 on the compressive stress-strain curve, in MPa;

[0094] σ2 represents the compressive stress corresponding to the strain value ε2 on the compressive stress-strain curve, in MPa;

[0095] ε1 represents the strain value at the calculation starting point, dimensionless;

[0096] ε2 represents the calculated endpoint strain value, which is dimensionless.

[0097] 6. Determination of battery fast charging performance

[0098] At 25°C, the batteries prepared in the examples and comparative examples were charged to 4.2V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage of 4.2V, and then discharged to 2.5V at a constant current of 0.33C after standing for 5 minutes, and the discharge capacity Q1 was recorded. Then, the battery is charged at 0.33C to a charge capacity of Q1×0.1, 4C to a charge capacity of Q1×0.8, 0.33C to 4.2V, 4.2V constant voltage charge to a current of 0.05C, and then discharged at 0.33C to 2.5V. After repeating the above charge and discharge process 20 times, the secondary battery is charged at 0.33C to a charge capacity of Q1×0.1, 4C to a charge capacity of Q1×0.8, 0.33C to 4.2V, 4.2V constant voltage charge to a current of 0.05C, and then the negative electrode sheet is disassembled and the lithium deposition on the surface of the negative electrode sheet is observed. Among them, the area of ​​lithium deposition on the negative electrode surface is less than 10%, which is considered to be slight lithium deposition, the area of ​​lithium deposition on the negative electrode surface is 10% to 50%, which is considered to be moderate lithium deposition, and the area of ​​lithium deposition on the negative electrode surface is greater than 50%, which is considered to be severe lithium deposition.

[0099] 7. Determination of battery energy density

[0100] At 25°C, the batteries prepared in each embodiment and comparative example were charged to 4.2V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage of 4.2V, and then discharged to 2.5V at a constant current of 0.33C after standing for 5 minutes, and the discharge capacity and discharge energy were recorded. The discharge energy divided by the weight of the battery is the weight energy density of the battery, in Wh / kg. The discharge energy divided by the volume of the battery is the volume energy density of the battery, in Wh / L.

[0101] 8. Determination of battery cycle performance

[0102] At 25°C, first charge at 1C constant current to 4.2V, then charge at 4.2V constant voltage to a current of 0.05C. After standing for 10 minutes, discharge at 1C constant current to 2.5V. Perform a cycle test in this full charge and discharge form until the discharge capacity of the lithium-ion battery decays to 80% of the initial capacity, and record the number of cycles at this time.

[0103] Test Results

[0104] Table 1

[0105]

[0106] It can be seen from Table 1 that the porosity P, surface density W, surface disorder D and orientation O of the negative electrode sheet satisfy the following relationship: 0≤3.6×P+2.6×D 0.5 -0.48×ln W-0.55×ln O≤0.75, which can ensure that the secondary battery has good fast charging performance, and has high weight energy density and volume energy density. The higher the porosity of the pole piece, the lower the surface density, the higher the surface disorder, and the lower the orientation, the better the fast charging performance of the battery. However, the higher the porosity and the higher the surface disorder, the lower the volume energy density of the battery; the lower the surface density and the higher the surface disorder, the lower the weight energy density of the battery. In other words, 3.6×P+2.6×D 0.5 -0.48×ln W-0.55×ln O<0, the fast charging performance of the battery is poor, 3.6×P+2.6×D 0.5 When -0.48×ln W-0.55×ln O>0.75, the weight energy density and volume energy density of the battery are low. In addition, the secondary battery of the present application further satisfies 15≤P×E≤45, which is beneficial to improve the cycle life of the battery.

[0107] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.

Claims

1. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, wherein the negative electrode active material comprises artificial graphite, and wherein the negative electrode sheet satisfies the following relationship: 0≤3.6×P+2.6×D 0.5 -0.48×ln W-0.55×ln O≤0.75, where P refers to the porosity of the negative electrode sheet; D refers to the surface disorder of the negative electrode plate, wherein the surface disorder is the intensity ratio of the D peak and the G peak of the artificial graphite; W refers to the surface density of the negative electrode sheet, in mg / cm 2 ; O refers to the orientation degree of the negative electrode plate, wherein the orientation degree is the peak area ratio of the diffraction peak of the 004 crystal plane of the artificial graphite to the diffraction peak of the 110 crystal plane.

2. The negative electrode sheet according to claim 1, characterized in that: 0≤3.6×P+2.6×D 0.5 -0.48×ln W-0.55×ln O≤0.6。 3. The negative electrode sheet according to claim 1, characterized in that: 15≤P×E≤45, wherein E refers to the compression modulus of the negative electrode plate, in MPa.

4. The negative electrode sheet according to claim 3, characterized in that: 20≤P×E≤40.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: It satisfies at least one of the following conditions: 15%≤P≤45% 0.1≤D≤0.6; 12≤W≤30; 3≤O≤20; 20≤E≤300。 6. The negative electrode sheet according to claim 5, characterized in that: 20%≤P≤45% 0.1≤D≤0.5; 15≤W≤25; 5≤O≤15; 30≤E≤200。 7. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The negative electrode active material also includes a silicon-based material.

8. The negative electrode sheet according to claim 7, characterized in that: The silicon-based material includes at least one of silicon, silicon alloys, silicon-carbon compounds, silicon-oxygen compounds, and a composite of elemental silicon and graphite. 9 . A secondary battery comprising the negative electrode sheet and the positive electrode sheet according to claim 1 . 10 . A device comprising the secondary battery according to claim 9 .